Book Reviews - AICKIN, MIKEL; DIAMOND, JR., ARTHUR M.; ORDMAN, EDWARD; KRIVIT, STEVEN B.; KAUFFMAN, JOEL M.; PHIPPS, JR., THOMAS E.; SMYTHIES, JOHN; BARUSS, IMANTS; SCHMICKER, MICHAEL; CLARK, STEPHEN R. L.; CORLISS, WILLIAM; GREENWOOD, BARRY; et al. (Journal of Scientific Exploration, 2010)
415 The Origin, Persistence, and Failings of HIV/AIDS Theory, by Henry H. Bauer - Mikel Aickin 419 The Black Swan: The Impact of the Highly Improbable, by Nassim Nicholas Taleb - Arthur M. Diamond, Jr. 422 Thinking about Go¨ del and Turing: Essays on Complexity, 1970–2007, by Gregory J. Chaitin - Edward Ordman 428 Voodoo Science: The Road from Foolishness to Fraud, by Robert L. Park - Steven B. Krivit 434 Climate Confusion: How Global Warming Hysteria Leads to Bad Science, Pandering Politicians and Misguided Policies that Hurt the Poor, by Roy W. Spencer - Joel M. Kauffman 436 Origin of Inertia: Extended Mach’s Principle and Cosmological Consequences, by Amitabha Ghosh - Thomas E. Phipps, Jr. 438 Muses, Madmen, and Prophets, by Daniel B. Smith - John Smythies 441 The Head Trip: Adventures on the Wheel of Consciousness, by Jeff Warren - Imants Baruss 442 The Witch in the Waiting Room: A Physician Investigates Paranormal Phenomena in Medicine, by Robert Bobrow - Michael Schmicker 443 The Trial of God, by John Smythies - Stephen R. L. Clark